The Impact of Authority Factors on Health Workers' Compliance with Hand Hygiene Practices at the Emergency Installation of Adi Husada Hospital, Undaan Wetan, Surabaya - Filip Yustinus Ongo; Nyoman Anita Damayanti (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Compliance with hand hygiene is a key National Quality Indicator established for hospitals and serves as a crucial metric for quality across all service units. The national target for hand hygiene compliance is set at over 85%. However, Adi Husada Hospital (AHUW) has set a higher target of 100% to meet the quality indicators for hand hygiene compliance. An analysis of hand hygiene compliance data from March to August 2024 revealed that the emergency department at AHUW achieved a compliance rate of 86%. This rate is lower than that of several other service units, such as the operating rooms (100%) and the intensive care unit (98%). This study aims to explore the relationship between authority factors and adherence to hand hygiene standard operating procedures (SOP) among health workers in the AHUW Emergency Installation. The research employed a quantitative, cross-sectional design and collected primary data via a questionnaire distributed via Google Forms. The study found that compliance among medical personnel at the AHUW Emergency Installation was rated good. The primary factor influencing both compliance and non-compliance was identified as the individual self-factor, followed closely by the organizational authority factor. Notably, only the location status showed a significant impact on handwashing compliance (p = 0.006). This finding suggests that the presence of authority figures in the workplace plays a crucial role in healthcare workers' adherence to hand hygiene practices. In contrast, the variables of responsibility, legitimacy, status, and proximity to authority figures did not exhibit significant effects (p > 0.05), suggesting they do not strongly influence compliance.These findings suggest that the visible presence of authority at the point of care is more impactful than any formal or perceived characteristics of that authority.  Keywords: compliance, hand hygiene, authority, health workers